MAKNA SIMBOLIK TRADISI MENDEM ARI-ARI MASYARAKAT JAWA JAMBI (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2023)
This research is motivated by the many meanings contained in each tradition found in the Javanese community in Suka Maju village. One of these traditions is the tradition of mendem ari-ari. The Mendhem Ari-ari tradition is a ritual ceremony for burying the placenta of a newborn baby in a certain way according to the customs of Javanese society. This tradition has been carried out since ancient times by ancestors, passed down from generation to generation and is still carried out today. This study used qualitative research methods. Researchers used observation, interviews and documentation methods to explore data in the field. The researcher used a purposive sampling technique to determine informants who met the researcher's criteria, then the researcher used source triangulation to check the validity of the data obtained. Researchers use Victor Turner's symbolic interpretation theory. The results of this research show that this tradition is a form of special treatment for the placenta because it is considered the baby's twin. This special treatment contains a certain meaning so that its implementation must really be done well, starting from the implementation process to the required objects such as salt, onions, garlic, perfume, needles, threads, combs, glass, pencils, books, etc. Arabic/Javanese writing paper, as well as coins, then the grave is sprinkled with flowers, covered with a basket and illuminated for eight (35) days. The treatment and objects used in the mendhem ari-ari tradition have meanings as a symbol of respect and hope from parents for their children.